RhIII-Catalyzed one-pot cascade synthesis of quinazolines with N-alkoxyamide as an amidating reagent. Issue 10 (7th April 2020) - Xu, Hui-Bei; Zhu, Yan-Ying; Yang, Jia-Hui; Chai, Xin-Yue; Dong, Lin
Abstract : Novel and efficient rhodium(iii )-catalyzed C–H bond activation and tandem annulation for the synthesis of structurally complex quinazolines have been successfully developed. Abstract : Novel and efficient rhodium(iii )-catalyzed C–H bond activation and tandem annulation for the synthesis of structurally complex quinazolines have been successfully developed. N -alkoxyamide as an amidating reagent was first used to construct this heterocyclic skeleton in one-pot cascade reaction.